Social Network User Profiling With Multilayer Semantic Modeling Using Ego Network - Jayapandian N; Tunze, Godwin Brown; Hamdi, Mounir; Tamil Selvi P; Balasubramaniam, Kishore; Vidhya S; Ramya K; Poongodi M (International journal of information technology and web engineering, 2022)
Social and information networks undermine the real relationship between the individuals (ego) and the friends (alters) they are connected with on social media. The structure of individual network is highlighted by the ego network. Egocentric approach is popular due to its focus on individuals, groups, or communities. Size, structure, and composition directly impact the ego networks. Moreover, analysis includes strength of ego – alter ties degree and strength of ties. Degree gives the first overview of network. Social support in the network is explored with the “gap” between the degree and average strength. These outcomes firmly propose that, regardless of whether the approaches to convey and to keep up social connections are evolving because of the dispersion of online social networks, the way individuals sort out their social connections appears to remain unaltered. As online social networks evolve, they help in receiving more diverse information.